Gods & monsters - Tsika, Noah, 1983- (Queer film classic., 2009)
Written and directed by Bill Condon (Dreamgirls), the 1998 film Gods and Monsters stars Ian McKellen as openly gay film director James Whale (best known for the Frankenstein films of the 1930s) in the final days of his life during the 1950s. Moving from the slums of Britain in the early twentieth century to the new era of "talkies" in Hollywood and beyond, Gods and Monsters trains a gay eye on the historical events that helped shape Whale and his films. Set in 1957, long after his career had peaked, he recounts his experiences to his young, straight gardener (played by Brendan Fraser.